Piezocision as an adjunct to orthodontic treatment of unilateral posterior crossbite - Bakathir, Manal A. (Saudi Med J, 2017)
Piezocision (corticotomy) is a minimally invasive approach that involves micro-incisions, piezoelectric incisions, and selective tunnelling for soft or hard tissue grafting. Piezocision has many uses in orthodontics, but its uses in cross-bite cases are limited. This case report illustrates the outcomes of a 19-year-old female patient with unilateral cross-bite that was treated with a minimally invasive piezocision with bone grafting in the affected side. In addition, she also had a functional shift, severe crowding, and mid-line shift. Therefore, the shift was eliminated using a quad helix expansion, she was treated with a fixed appliance, and a bimaxillary extraction of the first premolars was performed. The patient followed-up at 18 months, and the occlusion was stable with a pleasant profile. Piezocision can be used as an adjunct to the orthodontic treatment of adults to facilitate the treatment of complicated cases.